EFEKTIFITAS MASSAGE ENDORPHIN AROMATHERAPY LAVENDER DAN AROMATHERAPHY LEMONGRASS TERHADAP PRODUKSI ASI - Anita Indra Afriani; Indah Wulaningsih; Ernawati Ernawati (Jurnal Kebidanan, 2025)
Breastfeeding problems often faced by postpartum mothers are the release of breast milk in small amounts. Low breast milk production is a major problem for new mothers. The impact on babies who are not given breast milk is increased susceptibility to diseases such as ARI, diarrhea, coughs, colds, and will increase the number of morbidity and mortality in children. The solution that can be done in this problem is through pharmacological and non-pharmacological therapy. The purpose of this study was to determine the effectiveness of endorphin massage with lavender and lemongrass oils on breast milk production. The research method used in this study was quasi-experimental with two group pre-test and post-test. The number of samples for each group was 16 respondents with a total sample of 32 respondents. The sampling technique was simple random sampling. Bivariate analysis using the Wilcoxon test and the Mann Whitney test. Research Results: it is known that the Mann Whitney test shows a Pvalue of 0.010 <0.05 which means that there is a difference in the effectiveness of endorphin massage with lavender and lemongrass oils on breast milk production. The result of the mean rank is 12.25 and the endorphin massage with lemongrass is 20.75 so it can be concluded that the endorphin massage with lemongrass is more effective because the mean rank value is high.